Peranan Wali Kelas Sebagai Guru Bk Dalam Perkembangan Anak Mi Di MIN 1 Medan - Handayani, Fitri; Apriani, Yuli; Melati Putri, Rizki; Juaranas, Alnuris (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2024)
The research conducted at MIN 1 Medan aims to find out how important the role of guidance and counseling teachers is in dealing with problems experienced by students in elementary schools. However, in this case, the one who has duties and obligations in dealing with the problems faced by students at MIN 1 Medan is the class teacher. As someone who interacts most often with students, the homeroom teacher must be able to understand every aspect of the development experienced by students. The method that the author uses in this research is descriptive qualitative methods. By conducting interviews with several homeroom teachers at MIN 1 Medan, data was obtained which will then be analyzed in order to complete the data in writing. The research results show that the homeroom teacher at MIN 1 Medan has carried out his duties well. So that students' needs in their development have been met.